(untitled) (GANIT: Journal of Bangladesh Mathematical Society, 2017)
In this study, effect of boundary conditions on natural convection flow in an open cavity has been studied numerically. The computational fluid dynamics (CFD) simulations are performed to investigate the natural convection flow phenomena within the cavity. The ?-? turbulence model is chosen to capture the turbulence phenomena of the flow. A numerical case is chosen from literature to validate the method used in this study. For accurate prediction of the flow phenomenon a sufficiently large surrounding domain around the cavity is considered. The effects of boundary conditions applied in the apertures of the open cavity are observed. GANIT J. Bangladesh Math. Soc.Vol. 36 (2016) 47-58